Nanoporous anodic alumina with ohmic contact between substrate and infill: Application to perovskite solar cells. Issue 1 (16th November 2021) - Montero‐Rama, María P.; Viterisi, Aurelien; Ferré‐Borrull, Josep; Marsal, Lluis F.
Abstract: The use of a nanostructured aluminum substrate as the cathode for a perovskite photovoltaic device is described. This cathode consists of an aluminum substrate onto which a highly ordered array of aluminum oxide tubular pores was grown via anodization. The 1‐μm thick pores – arranged in a closed‐packed hexagonal pattern – were subsequently selectively etched at the bottom to remove the so‐called aluminum oxide barrier layer. The subsequent infiltration of the pores with the components of a methylammonium lead iodide perovskite solar cells, and the completion with a semi‐transparent anode, have shown to allow the establishment of an ohmic contact between the substrate itself and the components infiltrated into the Al2 O3 pores. Indeed, a clear rectifying behavior was observed on the full devices, as well as modest photovoltaic conversion efficiencies. This paper demonstrates that an ohmic contact can be established between the aluminum substrate from which nanoporous anodic alumina was grown, and that the pores can be used to compartmentalize the infill material down to the nanoscopic level. Abstract : Different materials were infiltrated nanoporous anodic alumina (NAA) with good control of their thickness and homogeneity. The aluminum base of NAA substrates was used as a back electrical contact for perovskite solar cells. A novel type of nanostructured perovskite solar cell based on NAA was manufactured.